The Strategic Role of the Department of Agriculture as a Regional Government Actor in the Development of Honey Bee Farming in Jayawijaya - herlyani; S, Herlyani; Difinuun, Muhammad Fagi; Wibowo, Didik Usman (Jurnal Honai, 2025)
The low capacity of farmers and suboptimal honey bee farming practices in Jayawijaya Regency necessitate strategic intervention from the local government. This study aims to examine the form of intervention by the Agriculture Office in strengthening honey bee farming, the effectiveness of the programs implemented, and the supporting strategies applied to increase the productivity and independence of farmers. The method used is a descriptive qualitative approach through field observations, in-depth interviews with farmers and extension workers, and documentation of activities.